Parsnip phytobezoar causing small bowel obstruction - Denise I. Garcia; William Taylor Head; Aaron P. Lesher (Elsevier, 2019)
Pediatric phytobezoars are a rare occurrence in the pediatric population and infrequently result in the need for surgical intervention. We report a rare case of an infant presenting with a small bowel obstruction that, on operative exploration revealed an obstructing parsnip phytobezoar. In addition, we provide a review of the literature for gastrointestinal bezoars causing bowel obstruction. Keywords: Bowel obstruction, Phytobezoar, Parsnip